PERHITUNGAN JEMBATAN KOMPOSIT SUNGAI MUARA BELINAU CALCULATION OF COMPOSITE BRIDGE MUARA BELINAU RIVER - RAHAYU, RAFI (KURVA S JURNAL MAHASISWA, 2013)
Transportation is an important part of the mechanism of human life and develop as human civilization it self. One part is the bridge transportation. The bridge is an important element in the transportation system, because the bridge function to serve the flow of traffic there on. The bridge was originally a wooden bridge, because the bridge is often the case that sway when there are vehicles passing above. Hence the need to improve the ability of the bridge and in the redesign of a composite bridge. Long-span composite bridge under review is 25 m, width 6 m carriageway, pavement width of 0.5 m and 0.5 m right side of the left side, so that the total width of the bridge is 7 m. Results of analysis of composite bridge calculation is derived calculations use the floor slab reinforcement for the D16-150 and D16 negative flexural-150 for flexural positive. Pavement using reinforcement D16-200. Pole using reinforcement 4Ø12 backrest. Tread plate for transverse and longitudinal directions using reinforcement D16-100.